Improved semi-empirical formula for cluster radioactivity half-lives - Liu, Xiao; Jiang, Jie-Dong; Li, Ming; Chen, Xun; Wu, Xi-Jun; Li, Xiao-Hua (International journal of modern physics. E, Nuclear physics, 2024)
An improved semi-empirical formula for cluster radioactivity half-lives is proposed by incorporating the influences of reduced mass, the blocking effect of unpaired nucleons and mass asymmetry on the basis of the original Tavares formula [Eur. Phys. J. A 49 (2013) 6]. Using this improved semi-empirical formula, the calculated results of the cluster radioactivity half-lives for the daughter nuclei around 2 0 8 Pb or its neighbors can reproduce the experimental data well with a corresponding root-mean-square deviation σ = 0.570, which proves the feasibility of this formula to calculate cluster radioactivity half-lives in trans-lead nuclei. The accuracy of the improved semi-empirical formula is improved by approximately 37% compared to its predecessor whose the root-mean-square deviation is 0.902. Meanwhile, the influence of deformation effect for cluster radioactivity is also briefly discussed. In addition, we extend this improved semi-empirical formula to predict the half-lives of 51 possible cluster radioactive candidates whose cluster radioactivity are energetically allowed or observed but not yet quantified in NUBASE2020. For comparison, some empirical and/or semi-empirical formulae are also used.